Implementation of Islamic Business Ethics in Laundry Services at Tarim Laundry Syariah Johor - Masthura, Nadia; Yusrizal, Yusrizal; Bi Rahmani, Nur Ahmadi (Tasharruf: Journal Economics and Business of Islam, 2024)
The purpose of this study is to look at how Islamic business ethics are being implemented in Islamic laundry services, using Tarim Laundry Syariah Johor as an example. Islamic business ethics plays a crucial part in the operation of businesses, especially laundry services. The descriptive qualitative research method was utilized, along with interview techniques, to gather information from company actors about the washing process, price transparency, and customer service. The findings revealed that Tarim Laundry Syariah is extremely concerned with honesty (As-Sidq) in protecting the sanctity of customer clothing and price transparency. Laundry Syariah can develop a healthy and mutually beneficial relationship with clients by committing to maintaining responsibility (Al-Amanah). Tarim Laundry Syariah always prioritizes a fair attitude (al-'adl) when dealing with consumers. Tarim Laundry Syariah is committed to employing environmentally friendly goods out of concern for the environment, or tazkiyah. Customers who receive good service (Ihsan) not only obtain what they need, but they also feel deeply satisfied since they interacted with a business that operates on strong ethical standards.